Radiation biophysics - Alpen, Edward L. (Academic Press, 1998)
This newly revised and updated edition of Radiation Biophysics provides an in-depth description of the physics and chemistry of radiation and its effects on biological systems. Coverage begins with fundamental concepts of the physics of radiation and radioactivity, then progresses through the chemistry and biology of the interaction of radiation with living systems. The Second Edition of this highly praised text includes major revisions which reflect the rapid advances in the field. New material covers recent developments in the fields of carcinogenesis, DNA repair, molecular genetics, and the molecular biology of oncogenes and tumor suppressor genes. The book also includes extensive discussion of the practical impact of radiation on everyday life. Key Features * Covers the fundamentals of radiation physics in a manner that is understandable to students and professionals with a limited physics background * Includes problem sets and exercises to aid both teachers and students * Discusses radioactivity, internally deposited radionuclides, and dosimetry * Analyzes the risks for occupational and non-occupational workers exposed to radiation sources.